Respuestas
Respuesta dada por:
6
TEOREMA DE PITÁGORAS:
![\boxed{hipotenusa^{2}=cateto^{2}+cateto^{2} } \boxed{hipotenusa^{2}=cateto^{2}+cateto^{2} }](https://tex.z-dn.net/?f=%5Cboxed%7Bhipotenusa%5E%7B2%7D%3Dcateto%5E%7B2%7D%2Bcateto%5E%7B2%7D+++%7D)
Revisa la imagen adjunta.
ESPERO QUE TE SIRVA.
Revisa la imagen adjunta.
ESPERO QUE TE SIRVA.
Adjuntos:
![](https://es-static.z-dn.net/files/d7c/430765aa17443c19dbf5159596acdaa1.jpg)
Respuesta dada por:
5
Formula:
(cateto₁)² + (cateto₂)² = (hipotenusa)²
Solución:
1)
(24 u)² + (32 u)² = x²
576 u² + 1024 u² = x²
1600 u² = x²
√(1600 u²) = x
40 u = x --->> Respuesta
2)
(27 u)² + (36 u)² = x²
729 u² + 1296 u² = x²
2025 u² = x²
√(2025 u²) = x
45 u = x --->> Respuesta
(cateto₁)² + (cateto₂)² = (hipotenusa)²
Solución:
1)
(24 u)² + (32 u)² = x²
576 u² + 1024 u² = x²
1600 u² = x²
√(1600 u²) = x
40 u = x --->> Respuesta
2)
(27 u)² + (36 u)² = x²
729 u² + 1296 u² = x²
2025 u² = x²
√(2025 u²) = x
45 u = x --->> Respuesta
inteligente70:
oye, faltan los triangulos
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años